Traits allowing some ant species to nest syntopically with the fire ant Solenopsis saevissima in its native range. (1st April 2014) - Dejean, Alain; Corbara, Bruno; Céréghino, Régis; Leponce, Maurice; Roux, Olivier; Rossi, Vivien; Delabie, Jacques H. C.; Compin, Arthur
Abstract: Supercolonies of the red fire ant Solenopsis saevissima (Smith) develop in disturbed environments and likely alter the ant community in the native range of the species. For example, in French Guiana only 8 ant species were repeatedly noted as nesting in close vicinity to its mounds. Here, we verified if a shared set of biological, ecological, and behavioral traits might explain how these 8 species are able to nest in the presence of S. saevissima . We did not find this to be the case. We did find, however, that all of them are able to live in disturbed habitats. It is likely that over the course of evolution each of these species acquired the capacity to live syntopically with S. saevissima through its own set of traits, where colony size (4 species develop large colonies), cuticular compounds which do not trigger aggressiveness (6 species) and submissive behaviors (4 species) complement each other.